Lessons from Scaling Up : Reducing Postharvest Loss through Mini Cold Storage Technology - Lessons from India - World Bank (Washington, DC, 2017)
The new 'lessons from practice: assessing scalability' report aims to provide specific tools and guidance to World Bank Task Team Leaders (TTLs) and other agricultural development specialists which can assist them in identifying the potential for scaling up small, innovative projects throughout the entire project cycle, from inception through completion. The report, developed in collaboration with the Heller school for social policy and management at Brandeis University, draws on lessons from the experience of the Development Marketplace (DM) in funding small innovation projects and offers strategic advice to agricultural practitioners on assessing the scalability of such projects. This note is based on a case study from India from the report.